Professional Status for Internal Auditors. - Campfield, William L. (The Accounting Review, 1965)
Abstract It is the purpose of this article to propose alternative paths for internal auditors in their quest for professional recognition. Antecedent to making recommendations, the writer briefly examines the key attributes of a profession and prepares an inventory of the plus and minus factors currently associated with the status of internal auditing. This article has been an inquiry into the current status of internal auditing. The writer has concluded that although internal auditors are not fully qualified as professionals they should be able to achieve such stature in the near future if they take certain adequately conceived and timely action. They need (1) to establish a uniform educational process, (2) to formulate and publish a code of professional standards, and (3) to develop a system of examination and accreditation of practitioners. There is a substantial body of preliminary data in these regards that has been developed over the years by individual internal auditors and by the Institute of Internal Auditors and its related chapters. This work needs to be synthesized and expanded as rapidly as possible.